Penentuan Lokasi Ideal SD dan MI Se-Kecamatan Pejagoan Kabupaten Kebumen dengan Menggunakan Model P-Median, P-Center, dan Max Covering - Ike Nurcahyono; I Wayan Suletra; Eko Liquiddanu (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2010)
Pejagoan district is an outskirt near the central administration of Kebumen Regency. This position causes some people prefer to go to city for schooling. This condition becomes one of the factors for decreasing number of students that apply to Pejagoan district. Many schools lacks of students. Kebumen Regency education department has a plan to reduce some schools that do not fulfill the criteria of minimum number of students. Determining ideal location and number of schools has to be appropriate in order to does not cause problems in the future. In this study, the determining of location and the number of school in Pejagoan district are conducted by identifying the location and the distance of students’ house to the location of current elementary schools that considered as candidate locations. The school locations and optimum number of school are determined by using three models, p-center, p-median, and maximal covering model. These are conducted to identify the performance of each model and compare all of them. The calculation result concluded that p-median model is the most appropriate model to solve the problem. The optimum number of school is 26 and the average distance of students to the nearest school is 215.98 meters with deviation standard 138.08 meters, and the furthest distance is 1229.3 meters.